Poly(urethane methacrylate-co-glycidyl methacrylate)-supported-polypropylene biphasic membrane for lipase immobilization - Pujari, N. S.; Vaidya, Bx; Bagalkote, S.; Ponrathnam, S.; Nene, Sanjay (Journal of Membrane Science, 2006)
Polypropylene (PP) was hydrophilized by coating followed by UV curing of a blend of 2-hydroxyethyl methacrylate (HEMA) terminated polyurethane prepolymer and glycidyl methacrylate (GMA). This allows formation of a hydrophobic membrane with increased surface hydrophilicity, biocompatibility and stability. Candida rugosa lipase (CRL) was covalently immobilized on this membrane using 5% glutaraldehyde as a crosslinking agent for post immobilization stabilization of enzyme on membrane. The membrane obtained was placed in a batch membrane reactor where a model esterification of oleic acid with octanol was studied. Under optimum conditions, the biocatalytic membrane gave a specific activity of 796.27 units/mg and 90.26% activity yield. Moreover, there was 85. 10% retention of specific activity. The biocatalytic membrane was observed to retain about 84.23% of its synthetic activity after six cycles. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Candida rugosa lipase; Enzyme immobilization; membrane bioreactor; urethane methacrylate

Immobilization of mushroom polyphenol oxidase on poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) macroporous beaded copolymers - Vaidya, Bhalchandra K.; Karale, Abhijeet J.; Suthar, Hitesh K.; Ingavle, Ganesh C.; Pathak, Tara Sankar; Ponrathnam, S.; Nene, Sanjay (Reactive & Functional Polymers, 2007)
Functional, macroporous, beaded copolymers containing epoxy groups were synthesized for immobilization of polyphenol oxidase (PPO) from edible mushroom (Agaricus bisporus). The effect of incorporation of two different sets of monomers such as glycidyl methacrylate (GMA) and allyl glycidyl ether (AGE) and the effect of cross-linking agent ethylene glycol dimethacrylate (EGDM) with varying cross-link densities on binding and expression of mushroom PPO activity were studied. The effect of porogen viz. cyclohexanol and hexanol on PPO immobilization was studied. AGE copolymers with hexanol as a porogen were found to give higher binding and expression of PPO activity than GE polymers. Crosslinking of amino groups of enzyme with 5% glutaraldehyde for 6 h gave a stable binding of PPO on AGE-75(Hex) polymer with storage half-life of approximately 25 days. Under optimum conditions, AGE-75(Hex) polymer gave 70.3% of activity yield while percent retention of PPO activity was found to be 83.5%. Immobilized PPO showed a broader pH, higher temperature and excellent storage stability. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: cross-linking agent; Enzyme immobilization; Epoxy-activated support; mushroom PPO

Integrated process for extraction and purification of alcohol dehydrogenase from Baker's yeast involving precipitation and aqueous two phase extraction - Madhusudhan, M. C.; Raghavarao, K. S. M. S.; Nene, Sanjay (Biochemical Engineering Journal, 2008)
The potential of aqueous two phase extraction for the purification of alcohol dehydrogenase (ADH) from Baker's yeast (Saccharomyces cerevisiae) is demonstrated. An integrated process involving precipitation followed by aqueous two phase extraction (ATPE) is used for effective recovery of the enzyme. This is carried out in two schemes. In the first scheme, ammonium sulphate precipitation is carried out followed by ATPE of the precipitate after suspending it in buffer. While the second scheme involves polyethylene glycol precipitation followed by ATPE of the supernatant. The effect of various process parameters such as molecular weight of polymer, tie line length, phase volume ratio and neutral salt is investigated for enhancing the activity recovery of ADH. First scheme resulted in about 85% enzyme activity recovery of ADH with purification factor of 4.2 while the second scheme about 90% enzyme activity recovery with 6.6-fold purification. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Alcohol dehydrogenase; aqueous two phase extraction; enzyme extraction; Precipitation; Purification; Yeast

Lipases catalyzed enantioselective hydrolysis of (R,S)-methyl 1,4-benzodioxan-2-carboxylate intermediate for (S)-doxazosin mesylate - Varma, Rita; Kasture, Sangita M.; Nene, Sanjay; Kalkote, Uttam R. (World Journal of Microbiology & Biotechnology, 2008)
(S)-1,4-benzodioxan-2-carboxylic acid-1 is used as starting compound for the production of the more effective (S) enantiomer of the drug doxazosin mesylate. The catalytic ability of some commercial lipases for preparations of (S) enantiomer of 1 from (+/-) methyl 1,4-benzodioxin-2-carboxylate-2 is reported. Lipases from bacterial sources were more successful in resolving the ester than those from the yeast lipases. About 85% enantiomerically pure ester was achieved by lipase from alcaligenes sp.
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; Enantioselectivity; Lipases

Influence of cultivar, ripeness, blanching, drying, irradiation, and pectin recovery on alk(en)ylresorcinols in mango peels - Geerkens, Christian Hubert; Miller-Rostek, Petra; Matejka, Anna Elisabeth; Nene, Sanjay; Kammerer, Dietmar Rolf; Carle, Reinhold; Schweiggert, Ralf Martin (European Food Research and Technology, 2015)
The influence of different technological treatments on alk(en)ylresorcinol (AR) contents and pattern in mango peels was evaluated using peels from six different mango cultivars. AR concentrations were shown to highly depend on the cultivar. While high AR concentrations were observed in the analyzed monoembryonic cultivars, AR contents in the polyembryonic cultivar Nam Dokmai were significantly lower. Furthermore, for monoembryonic cultivars, AR levels in the peels of ripe fruits were found to be higher than in unripe ones, while AR levels in cv. Nam Dokmai were independent of the ripeness degree. Convective oven drying resulted in a significant reduction in AR contents when compared to lyophilization. Blanching prior to drying diminished AR yields, thus being unsuitable for satisfactory AR recovery. Gamma irradiation did not significantly affect the AR contents. Since depectinization of mango peels significantly concentrated AR amounts in the depectinized pomace, the consecutive extraction of pectin and ARs allows the dual valorization of mango peels. Considering the treatments investigated, the retention of ARs carrying saturated and unsaturated side chains did not differ under acidic conditions, heating, and irradiation, respectively. Consequently, the 1,3-dihydroxybenzene structure was concluded to be the most labile moiety of the AR molecule.
Keywords: Alkylresorcinol; By-products; Monoembryonic; Polyembryonic; Pomace; Ultrasound

Production of polyunsaturated fatty acids in recombinant lipomyces starkeyi through submerged fermentation - Salunke, Devyani; Manglekar, Rupali; Gadre, Ramchandra V.; Nene, Sanjay; Harsulkar, Abhay M. (Bioprocess and Biosystems Engineering, 2015)
Long chain polyunsaturated fatty acids (LCPUFA) are known to play an important role in human health and nutrition. Considering the limitation of LCPUFA sources, it is necessary to search new avenues for their production. Oleaginous yeasts are an attractive target for harvesting single cell oil, mainly because of the ease of cultivation with cheaper raw material. Lipomyces starkeyi is one such oleaginous yeast, which can accumulate oil to the extent of 60 % of its biomass and where genetic transformation can be achieved. In our earlier work, Delta 15 desaturase gene (AEP37840) from flax was transformed into L. starkeyi. In the present work, we report optimization of medium for the production of omega-3 enriched oil from this transformed yeast. A basic medium containing 20 g/l glucose as a carbon source and 10 g/l yeast extract as a nitrogen source was used during fermentation. At regular time intervals, glucose was fed to maintain high C:N ratio (65:10) during fermentation. Under the most favorable conditions, dry biomass and total lipid content were 18 and 7.29 g/l, respectively. Prior to genetic transformation, L. starkeyi contained 56.03 mg/l DHA along with 71.4 mg/l EPA and 42.2 mg/l ALA. Genetic engineering of this yeast resulted in a strain that produced 1080 mg/l DHA (17.4 %) along with 74.28 mg/l EPA and 126.72 mg/l ALA possibly through modification of PUFA biosynthetic pathway. To the best of our knowledge, this is a first report of DHA enrichment and opens up avenues for LCPUFA production through L. starkeyi.
Keywords: Fermentation; LCPUFA; Lipid production; Oleaginous yeast

Kinetic studies on an algal biofilm reactor for raw sewage water treatment - Gera, Gayatri S.; Yewalkar, Swati N.; Nene, Sanjay; Kulkarni, Bhaskar D.; Kamble, Sanjay P. (Chemical Engineering & Technology, 2016)
A packed-bed algae biofilm reactor was developed using porous and nonporous dual packings. The biofilm was cultivated on reticulated polyurethane foam cubes. The nonporous glass Raschig rings were taken as bed support that helps to remove generated gas from the system. The effect of variables such as column length-to-diameter ratio, catalyst cube dimension, and feed flow rate on the treatment of sewage water was studied. The reaction kinetics indicates that the nutrients uptake rate is dependent on both pore and film diffusion. The kinetics of uptake of nutrients follows a pseudo first-order reaction. From the pseudo reaction rate constant, Thiele modulus and effectiveness factor were calculated and a kinetic model equation for fractional nutrient uptake was developed in terms of operating variables. The model can predict the reaction rate with low deviation. The results obtained may be valuable for large-scale treatment of sewage water.

Exploiting phosphate-starved cells of scenedesmus SP for the treatment of raw sewage - Yewalkar-Kulkarni, Swati; Gera, Gayatri; Nene, Sanjay; Pandare, Kiran; Kulkarni, Bhaskar; Kamble, Sanjay (Indian Journal of Microbiology, 2017)
Phosphate depletion is one of the favorable ways to enhance the sewage water treatment with the algae, however, detailed information is essential with respect to internal phosphate concentration and physiology of the algae. The growth rate of the phosphate-starved Scenedesmus cells was reduced drastically after 48 h. Indicating cells entered in the stationary phase of the growth cycle. Fourier Transform Infrared analysis of phosphate-starved Scenedesmus cells showed the reduction in internal phosphate concentration and an increase in carbohydrate/phosphate and carbohydrate/lipid ratio. The phosphate-starved Scenedesmus cells, with an initial cell density of, 1 x 10(6) cells mL(-1) shows 87% phosphate and 100 % nitrogen removal in 24 h. The normal Scenedesmus cells need approximately 48 h to trim down the nutrients from wastewater up to this extent. Other microalgae, Ankistrodesmus, growth pattern was not affected due to phosphate starvation. The cells of Ankistrodesmus was able to reduce 71% phosphate and 73% nitrogen within 24 h, with an initial cell density of, 1 x 10(6) cells mL(-1).
Keywords: Ankistrodesmus; Fourier Transform Infrared; Phosphate starvation; Scenedesmus; Sewage treatment

Comparison of hydrodynamic characteristics of Tulsion and Siran immobilised beads in a fluidised bed bioreactor - Kashid, Shweta; Joshi, Kalpana; Nene, Sanjay (Biocatalysis and Agricultural Biotechnology, 2022)
<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">The fluidised bed reactors are successfully utilised in various bioprocesses to produce <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/high-value-products" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about high value products from ScienceDirect's AI-generated Topic Pages">high value products using <a class="topic-link" href="https://www.sciencedirect.com/topics/immunology-and-microbiology/immobilized-cell" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about immobilised cells from ScienceDirect's AI-generated Topic Pages">immobilised cells and enzymes. The present work aims at evaluating hydrodynamic characteristics of a three phase fluidised bed <a class="topic-link" href="https://www.sciencedirect.com/topics/immunology-and-microbiology/bioreactor" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about bioreactor from ScienceDirect's AI-generated Topic Pages">bioreactor using Tulsion® A-1X MP, Tulsion® ADS-400 and Tulsion® ADS-800, <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/polystyrene" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about polystyrene from ScienceDirect's AI-generated Topic Pages">polystyrene and polyacrylic based three types of free and <a class="topic-link" href="https://www.sciencedirect.com/topics/immunology-and-microbiology/immobilized-cell" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about immobilised cells from ScienceDirect's AI-generated Topic Pages">immobilised cells solid carriers viz. and comparing their performance with Siran® SIKUG41 glass beads. The hydrodynamic parameters such as particle density (cells and beads), drag coefficient, minimum and maximum <a class="topic-link" href="https://www.sciencedirect.com/topics/immunology-and-microbiology/fluidization" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about fluidisation from ScienceDirect's AI-generated Topic Pages">fluidisation velocity, particle settling velocity were estimated and compared in water and biological media (E2 and MSM) having varying rheological properties. The relationships between drag coefficient (C<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif;">D<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">)–Reynolds numbers (N<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif;">Re<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">), superficial liquid velocity (U<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif;">f<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">)–void fraction(ε), expansion index(n)–N<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif;">Re<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;"> were obtained.